Hypersonic Aeroelastic Response of Elastic Boundary Panel Based on a Modified Fourier Series Method - Xiyue Zhou; Lifeng Wang; Jingnong Jiang; Zhu Su (International Journal of Aerospace Engineering)
In this paper, an analytical method is proposed to directly obtain the aeroelastic time domain response of the elastic boundary panel. Based on a modified Fourier series method (MFSM), the vibration analysis of elastic boundary panels is carried out, after the dynamics equation of the panel is obtained. Then, the vibrational functions are combined with the supersonic piston theory to establish the aeroelastic equation. The aeroelastic time domain response of the panel is obtained to analyze the flutter speed of the panel more intuitively. Finally, the flutter speeds of panels with different length-width ratios, thicknesses, and elastic boundary conditions are discussed in detail.